2017
DOI: 10.1097/md.0000000000007190
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal bupivacaine versus traditional bupivacaine for pain control after total hip arthroplasty

Abstract: Background:In the past, the efficacy of local infiltration of liposomal bupivacaine for total hip arthroplasty (THA) patients was in debate. Therefore, this meta-analysis was conducted to determine whether local infiltration of liposomal bupivacaine provides better pain relief after THA.Methods:We searched Web of Science, PubMed, Embase, and the Cochrane Library databases to the April 2017. Any studies comparing liposomal bupivacaine and traditional bupivacaine were included in our meta-analysis. The outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 21 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…Our findings are similar to the results found by Domb et al, 8 which demonstrated significant decreases in opioid consumption and hospital LOS when patients received periarticular LB versus the control group who received plain bupivacaine. These findings are also consistent with a recent meta-analysis by Ma et al, 20 further demonstrating reductions in opioid consumption and hospital length of stay. Further randomised, controlled studies are needed to clarify the total difference in costs between patients who receive LB periarticular injections versus a non-LB cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are similar to the results found by Domb et al, 8 which demonstrated significant decreases in opioid consumption and hospital LOS when patients received periarticular LB versus the control group who received plain bupivacaine. These findings are also consistent with a recent meta-analysis by Ma et al, 20 further demonstrating reductions in opioid consumption and hospital length of stay. Further randomised, controlled studies are needed to clarify the total difference in costs between patients who receive LB periarticular injections versus a non-LB cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Although this is a novel finding for the perineural route, it may not be totally new for liposomal bupivacaine. Several recent systematic reviews 27,30,[89][90][91][92][93][94][95][96][97] and an editorial 29 examining the evidence for surgeon-administered local infiltration analgesia using liposomal bupivacaine have questioned its effectiveness. Curiously, the underlying causes of both perineural and infiltration routes failing to provide incremental benefits when compared with nonliposomal bupivacaine, 98,99 and even placebo (normal saline), 12 may be similar.…”
Section: Discussionmentioning
confidence: 99%
“…THA Two MAs compare LB to plain bupivacaine-PAI for THA [62,111]. In both, LB significantly reduces pain scores and opioid consumption up to 48 h after THA.…”
Section: Continuous-release Local Anestheticsmentioning
confidence: 99%